Exploring Interpersonal Communication on Affective Commitment: Cross Sectional Study on Teacher Perspective - Asmawati Asharie (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2021)
This study intends to determine the effect of internal communication aspects on affective commitment. To determine the influence of the interpersonal communication aspect, the researcher used a survey of private high school teachers in Palembang City, South Sumatra. The number of respondents was as many as 137 teachers. To examine the effect of interpersonal communication aspects on affective commitment, researchers used multiple regression analysis techniques. The results showed that all aspects of interpersonal communication had a significant effect on teachers' affective commitment. In addition, the study results indicate that excellent openness, empathy, supportiveness, positiveness, and equality will impact teachers' affective commitment.